THE INFLUENCE OF INNOVATION ADOPTION AND MARKETING MIX ON THE PURCHASE DECISION OF ELECTRIC VEHICLES AMONG CONSUMERS IN THE EASTERN SEABOARD INDUSTRIAL AREA, RAYONG PROVINCE - Rotthong, Nopadon; Lapsomboondee, Ampinee (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This research aimed to study: (1) The decision-making of consumers in the Eastern Seaboard Industrial Estate, Rayong Province to purchase electric vehicles, (2) The factors of product innovation acceptance and marketing mix that influenced the demand and decision-making process of consumers to purchase electric vehicles in the Eastern Seaboard Industrial Estate, Rayong Province, and (3) The policies to support and promote the use of electric vehicles that influenced the demand and decision-making process of consumers to purchase electric vehicles in the Eastern Seaboard Industrial Estate, Rayong Province. This research was quantitative research. The sample group was 400 consumers in the Eastern Seaboard Industrial Estate. The research instrument was a questionnaire. The statistics used frequency, percentage, mean, standard deviation, Pearson's correlation, and logistic regression analysis. The research results found that (1) The decision to purchase electric vehicles of consumers in the Eastern Seaboard Industrial Estate, Rayong Province, found that most respondents decided to purchase electric vehicles, 263 people, or 65.7%. 2) The variables entered into the equation for forecasting the demand for electric vehicles of consumers in the Eastern Seaboard Industrial Estate, Rayong Province, with a significance level of .05 were occupation, product, and location respectively. It was found that the variables entered the equation for forecasting the demand for electric vehicles of consumers in the Eastern Seaboard Industrial Estate, with a significance level of .01 were comparative benefits and government policies respectively. These independent variables could jointly explain the variance in the demand for electric vehicles of consumers in the Eastern Seaboard Industrial Estate, Rayong Province, by 34.50%.